Histidinemia in preschoolers with communication disorders - Beltrán, Denia; López, Marcia de la Caridad; Contreras, Jiovanna; Quintana, Daniel; Fuentes, Lisset; Hernández, Orietta; Alonso, Elsa; Escalona, Ondina; Morales, Estela (Revista de Investigación en Logopedia, 2013)
Speech disorders are a common the most common causes of the Logopedia and Phoniatry consultation during childhood, point at which the specialist perform the clinic functional examination to find the etiology in order to begin an effective rehabilitation treatment. The specific language impairment and speech are among the speech disorders of unknown cause. Histidinemia is frequently associated with speech disorders. An analytical case-control study was developed in 27 cases with speech disorders and 102 controls. The concentration of histidine in serum of all children was determined by an ultramicroanalytic method. The histidine levels were elevated in the 29.6% of the case group and only in the 1.0% of the control group. The histidine level difference is more significant among between the language impairment group and the control group, while children with dyslalia did not differ significantly with the children with specific language impairment and the control groups. These results showed that histidine levels are likely to be more elevated in children with speech disorders than in the control group.
Keywords: Histidine; Histidinemia; Specific language impairment.